Voicing heartbreak: The sociopragmatics of ‘Cidra’ and Javanese masculinity in Didi Kempot’s lyrics - Iswatinginsih, Daroe; Tuan, Nguyen Thanh; Diana, Purwati Zisca; Rahmawati, Ida Yeni; Firmansyah, Ridho Covinda Wahyu (BAHASTRA, 2025)
This study investigates the representation of cidra (heartbreak or betrayal of promise) and the construction of Javanese masculinity in Didi Kempot’s song lyrics through a sociopragmatic approach. Drawing on seven songs from four albums, the analysis proceeds in three steps: (1) segmenting the lyrics into expressive speech acts, (2) interpreting them through affective cultural scripts, and (3) situating the findings within masculinity discourses. The results reveal a tripartite model of male emotionality: (1) loyalty and patience that affirm Javanese cultural values, (2) emotional fragility expressed through crying and complaint, which challenges the script of stoic masculinity, and (3) resignation (lilo) as a culturally sanctioned coping mechanism. These dimensions converge into the concept of hybrid masculinity, which reconciles normative ideals with emotional expressions previously deemed inappropriate for Javanese men. Theoretically, this study contributes a sociopragmatic framework for analyzing emotional speech acts in non-Western contexts and positions popular music not only as a reflection but also as a site for reshaping gender norms. Practically, it demonstrates how Didi Kempot’s songs function as a form of collective cultural therapy, offering insights for culturally sensitive approaches to men’s mental health.